Sociology of legal subjectivity - Guibentif, P. (Research handbook on sociology of law, 2020)
Summary: It is argued here that the concept of “legal subjectivity” should be recognized as an indispensable piece of sociology of law’s theoretical tool kit, designating a priority research domain. In defence of this argument, the concept is specified, critiques that were addressed to it throughout the recent history of sociology of law are discussed, and a conceptual framework is presented, with a view to its empirical operationalization. This conceptual framework, inspired by systems theory, approaches a certain form of subjectivity as a characteristic of modernity, located at the interface between communication and individual psychic activity. Apart from applications to crucial contemporary issues – such as changes in the experience of citizenship, their causes and their possible consequences – it could help sociology of law to better contribute to a reflexive research about current changes in the scientific field itself.